Design and Evaluation of a 3D Pop-Up Textbook with Finger Puppets for Thematic Learning in 10-11 Year Olds - Ajie Pangestu Ganiansyah; Nurul Hidayah; Antomi Saregar (Smart Society, 2024)
Thematic learning in elementary schools requires innovative instructional media to enhance student engagement and comprehension. However, the lack of interactive and engaging learning media often results in student disengagement and low participation. This study aims to develop, validate, and assess the practicality of a three-dimensional (3D) learning medium that integrates pop-up book features and finger puppets as visual and kinesthetic learning aids. The research employs the ADDIE development model, comprising five phases: Analysis, Design, Development, Implementation, and Evaluation. The participants included 10–11-year-old students from MIN 1 Bandar Lampung and SDN 1 Pajaresuk. Data collection was conducted through interviews, observations, questionnaires, and document analysis. Validation results indicated that the learning medium was highly feasible, with average scores of 93% from two content experts, 81% from two media experts, and 89% from two language experts. Practicality assessments by two educators yielded an average score of 98%, while small-scale and large-scale trials resulted in scores of 89% and 94%, respectively. These findings suggest that the developed 3D learning medium is both feasible and effective for thematic learning in elementary schools, offering a promising approach to enhancing student engagement and learning outcomes.